Teachers’ Constrains in the Learning Process at Junior High School during Covid-19 Pandemic in Banda Aceh - Marwan Marwan; Jalaluddin Jalaluddin; Fakhrul Rijal; Ibrahim Ibrahim (STAI Hubbulwathan Duri, 2023)
This research looks at the difficulties middle school educators face in Banda Aceh City, Indonesia, due to the covid-19 pandemic. The purpose of this investigation is to report on the challenges that emerged during the pandemic for a relatively new method of education: online study. Three public middle schools in Banda Aceh are the subjects of this study. Data is gathered through observation, interviews, and record-keeping, all hallmarks of qualitative research methods. The results show that teachers face a number of challenges when implementing online learning, including difficulties in adaptation because teachers cannot directly control their students' activities in order to assess them objectively; teachers' lack of understanding of technology, especially among older educators; teachers' encounters with passive students; teachers' less stable networks, which cause internet data quotas to become wasteful during online learning; and teachers' lack of control over their students' access to the internet, which makes it difficult to enforce strict rules and regulations.